User preference for fixed vs. mobile internet regarding quality of service: Its implications on mobile network neutrality - Toshiya Jitsuzumi (International Telecommunications Society (ITS), 2011)
The rapid development of information and communication technology has facilitated Internet use considerably, particularly with regard to the speed of packet transfer at access segments. With the boom in bit-intensive and live-streaming content in the broadband Internet ecosystem, the phenomenon of increasing and persisting congestion on the Internet is no longer a mere engineering possibility but a grave and imminent reality. To deal with this problem, network neutrality has become the focus of discussion among operators, academics, and telecom regulators in recent years. Over the past several months, one of the most contentious issues in the US discussion of network neutrality has been whether both mobile and fixed Internet access should comply with similar network neutrality standards. Unfortunately, thus far, policy has been developed and academic debates have taken place without an understanding of the extent to which fixed and mobile Internet services are, from the user's perspective, close substitutes. Therefore, it is impossible to determine whether it is beneficial to treat these services similarly. Using a Web-based questionnaire, this paper shows empirically that users' communication quality preferences for fixed broadband differ significantly from their preferences for its mobile counterpart, suggesting that different treatments should be proposed for each broadband medium in order to attain optimal resource allocation.
Keywords: 330